Tinjauan Pelaksanaan Program Pencegahan Stunting di Puskesmas Manutapen - Darince Bire Lay; Rina W. Sirait; Galuh Larasati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Stunting is a condition of impaired growth and development in children due to chronic malnutrition, characterized by a height-for-age index below -2 SD according to WHO standards. The Kupang City Health Office reported an increase in stunting cases at the Manutapen Health Center from 149 to 194 cases. This study aims to evaluate the implementation of the stunting prevention program at the Manutapen Health Center in 2024. A qualitative descriptive method with an evaluative approach was used, employing in-depth interviews as the primary data collection technique. Informants were selected using purposive sampling, which emphasizes the quality, credibility, and richness of information over the quantity of participants (Nitbani, 2019). Findings show that in the input component, human resources meet the required standards; however, insufficient funding and inadequate facilities and infrastructure hinder program optimization. In the process component, planning is carried out by the health office, with clear task distribution among staff. While implementation is running fairly well, the participation of mothers with toddlers remains low, necessitating improved supervision and evaluation mechanisms. As for the output, the program has not yet achieved the targeted reduction in stunting rates. Enhancing budget allocation in line with the number of beneficiaries, providing adequate SDIDTK tools at each posyandu, and ensuring continuous assistance and monitoring for mothers in administering supplementary feeding (PMT) at home are urgently needed.